Exploring the Motivations, Challenges, and Impacts of Women Entrepreneurs in Developing Societies: An Exploration of Online University - Binazir Mubariz; Nafisa Wafa; Asiya Jalali; Sara Afif Sahel; Roqia Sadat; Tamanna Quraishi (International Journal of Management Science, 2025)
This study explores the role of entrepreneurship in achieving financial independence and fostering community development, with a specific focus on gender and societal norms. The problem addressed is the challenges faced by women entrepreneurs due to cultural expectations, limited access to resources, and difficulties in balancing family responsibilities with business operations. The purpose of this research is to examine how women-led businesses contribute to financial independence and whether societal norms support or hinder their entrepreneurial endeavors. A stratified random sampling method was used to select 180 participants, including both male and female entrepreneurs from diverse industries and geographical regions. Data was collected using a structured survey with Likert-scale and open-ended questions, and analyzed using descriptive and inferential statistics to identify trends and challenges. The results indicate that entrepreneurship is widely seen as a pathway to financial independence. However, many respondents, particularly women, reported challenges in securing funding and balancing business with family obligations. Despite these obstacles, women-led businesses were found to significantly contribute to community development by providing employment and creating opportunities for others. In conclusion, while women entrepreneurs face substantial barriers, their businesses play a vital role in both economic and social empowerments. Policy interventions that address these challenges are necessary to fully harness the potential of women-led entrepreneurship.